As rare as hen's teeth: aberrantly coloured eggs of the northern lapwing (Vanellus vanellus) and the interface between oology and ornithology. Issue 1 (31st December 2022) - Birkhead, T. R.
Abstract: The majority of birds lay eggs of a colour and maculation "typical" of their species, but very occasionally individual females produce eggs of unusual colours. In the past, such eggs were often the target of egg collectors. Four trays of unusually coloured northern lapwing Vanellus vanellus eggs originally accumulated by two notable collectors, F.C.R. Jourdain and J. M. Goodall in the late 1800s and early 1900s, were recovered from the home of David Wilson after his death in 2020. Wilson had acquired this lapwing material, comprising 91 clutches and 347 eggs in total, from the avid collector and millionaire, Captain Vivian Hewitt after Hewitt's death in 1965. The lapwing clutches are unusual both in terms of their colours, ranging from pale blue with almost no maculation ("cyanic"), through to red ("erythristic"), but also in terms of the completeness of their accompanying data. During the 1800s and early 1900s, hundreds of thousands of lapwing eggs were collected annually in Britain and the Netherlands for human consumption, providing egg collectors, like Goodall and Jourdain, the opportunity to screen large numbers of clutches and acquire rare types. The occurrence of rare egg types in museum egg collections have the potential to provide opportunities to better understand the normal physiological and genetic bases of avian egg colour.